The relationship of socio-demographic characteristics and breast cancer knowledge on the stage of behavioral adoption of breast self-examination - Aaina Mardhiah Abdul Mutalib (Kulliyyah of Allied health Science, International Islamic University Malaysia, 2020)
In Malaysia, breast cancer is the most common cancer amongst women. As such, early diagnosis and screening practice is important to increase the survival rate. Breast self-examination (BSE) is one of the main screening methods for breast cancer. However, socio-demographic characteristics and knowledge of breast cancer are amongst the crucial factors in determining women's behavioral adoption of BSE. Thus, this study aims to assess the association of socio-demographic characteristics and knowledge of breast cancer on the behavioral adoption of BSE amongst Malaysian women in Kuantan, Pahang. A cross-sectional study was conducted on 520 women from three different government health clinics in Kuantan and IIUM Family Health Clinic from February to April 2018. Data were collected using a self-administered questionnaire on socio-demographic characteristics and knowledge of breast cancer and its effect on the behavioral adoption of BSE. Significant differences were found between socio-demographic characteristics and behavioral adoption of BSE. The study found that women below the age of 50 years (p-value<0.01) and married (p-value=0.01) are more likely to believe that BSE is beneficial. Additionally, women with higher education (p-value=0.01) and income (p-value<0.01) possibly have better access to information and the as such the likelihood of performing BSE. However, for breast cancer knowledge, breast screening and best time for screening were the only two attributes found to be significant with the behavioral adoption of BSE. This study found that most women in Kuantan, Pahang perform BSE but were still unaware of its' importance as a method for early detection of breast cancer as most of them were not able to detect breast lump, an essential aspect of BSE. Data obtained from this study can be used to create awareness pertaining to breast cancer as well as to enhance breast health promotion for early breast cancer detection. Keywords: Breast cancer, breast self-examination, socio-demographic, knowledge, Stage of Change Theory